2006
DOI: 10.1016/j.tiv.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation of individual and combined cytotoxic effects of ochratoxin A and other selected mycotoxins on renal cells

Abstract: Hundreds of mycotoxins are known to date and many of them are of great interest with regard to human and animal health since they are detected frequently in plant-derived products. Various mycotoxins may occur simultaneously, depending on the environmental and substrate conditions. Considering this coincident production, it is very likely, that humans and animals are always exposed to mixtures rather than to individual compounds. Therefore, future risk assessments should consider mixture toxicity data. This is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(69 citation statements)
references
References 25 publications
4
61
1
3
Order By: Relevance
“…At first, this appeared to stand in contrast to literature data including our own earlier findings Heussner et al, 2006;O'Brien et al, 2001). The latter data showed a higher toxicity of OTA compared to that of OTB in various renal cell types, however these data always originated from single time-point short-term investigations.…”
Section: Discussioncontrasting
confidence: 94%
“…At first, this appeared to stand in contrast to literature data including our own earlier findings Heussner et al, 2006;O'Brien et al, 2001). The latter data showed a higher toxicity of OTA compared to that of OTB in various renal cell types, however these data always originated from single time-point short-term investigations.…”
Section: Discussioncontrasting
confidence: 94%
“…Recent CIT research is oriented toward nephrotoxicity; both additive and synergistic effects have been described in combination with OTA (ref. 61,[63][64][65] ). With regard to the nephrotoxicity of CIT, the situation may be complicated by the fact that CIT interacts with other naturally occurring mycotoxins e.g.…”
Section: Etiologymentioning
confidence: 99%
“…For binary mixtures involving OTA, additive toxic effects were observed for combinations with AFB 1 in kidney cells (Golli-Bennour et al, 2010) and in hepatoma-derived cells (Corcuera et al, 2011), whereas synergistic effects were reported in rat brain glioma, Caco-2 and Vero cells (Creppy et al, 2004); antagonism was described for the combined toxicity of OTA and AFM 1 in Caco-2 cells (Tavares et al, 2013). In addition, synergistic effects between OTA and CIT were identified in renal cells in vitro (Bouslimi et al, 2008;Heussner et al, 2006) and in vivo (Pfohl-Leszkowicz et al, 2008). Recently, the effect of the ternary mixture of OTA, citrinin and sterigmatocystin was explored in a human hepatocellular cancer cell line (Hep3B), showing a synergistic effect at low toxin doses that shifted to antagonism at higher concentrations (Αnninou et al, 2014).…”
Section: Evaluation Of Combined Effects Of Multiple Mycotoxinsmentioning
confidence: 99%